2011
DOI: 10.1037/a0025293
|View full text |Cite
|
Sign up to set email alerts
|

How are depression and autobiographical memory retrieval related to culture?

Abstract: This study investigated how culture influences the association between autobiographical memory retrieval and depression. Thirty clinically depressed patients and 30 controls, 15 each from Britain and Taiwan, completed the English and Chinese versions of the Autobiographical Memory Cueing Task (AMT). Overall, the depressed individuals from both cultural groups retrieved significantly fewer specific and more categoric autobiographical memories than their matched, nondepressed controls. Within the control groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
(40 reference statements)
0
18
0
2
Order By: Relevance
“…It turns out that OAM are observed in the people suffering from rDD regardless of age and are probably independent of culture . According to Woody et al ., the OAM are also found in the children of mothers who are treated due to depression (in response to verbal stimuli of a negative emotional charge).…”
Section: Am In Recurrent Depressive Disordersmentioning
confidence: 97%
“…It turns out that OAM are observed in the people suffering from rDD regardless of age and are probably independent of culture . According to Woody et al ., the OAM are also found in the children of mothers who are treated due to depression (in response to verbal stimuli of a negative emotional charge).…”
Section: Am In Recurrent Depressive Disordersmentioning
confidence: 97%
“…Some studies have showed that the increased use of pesticides is associated with an increase in suicides [11, 12], and easy access to lethal pesticide is a significant risk factor for suicide [13]. Therefore, some studies have suggested that a ban of lethal pesticides in rural areas can be a method for suicide prevention [14].…”
Section: Introductionmentioning
confidence: 99%
“…Potential participants ( N = 353) were screened using an online questionnaire to assess eligibility. Adopting the approach of previous cross‐cultural clinical research (e.g., Dritschel, Kao, Astell, Neufeind, & Lai, ; Grossmann & Kross, ; Jobson, Moradi, Rahimi‐Movaghar, Conway, & Dalgleish, ), participants identified as either European Australian (with all four grandparents being of European Australian descent) or East Asian (with all four grandparents being of East Asian descent and living in Australia for < 5 years). Eligibility criteria also included being aged between 18 and 60 years and no history of substance dependence, bipolar disorder, traumatic brain injury, neurological illness, psychosis, or PTSD (as indexed by scoring 33 or above on the PTSD Checklist for DSM‐5, Blevins, Weathers, Davis, Witte, & Domino, ).…”
Section: Methodsmentioning
confidence: 99%